1999
DOI: 10.1073/pnas.96.8.4252
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of the parity-violating energy difference between enantiomers

Abstract: Racemic mixtures of (؉) and (؊) sodium potassium tartrate, tris(1,2-ethanediamine)cobalt(III), and tris(1,2-ethanediamine)iridium(III) molecules were crystallized, and the optical activities of the resulting crystalline materials, dissolved in water, were carefully measured to study the inf luence of the parity-violating energy difference in the crystallization process. Although no effect was found in the case of tartrate, enantiomeric excess appeared in the crystallization of the cobalt and iridium complexes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
45
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(48 citation statements)
references
References 28 publications
3
45
0
Order By: Relevance
“…5 Szabo-Nagy and Keszthelyi 59 claimed to detect a parity-violating difference in the CD spectra of cobalt(III) and iridium (III) salts of tris(ethanediamine). Wang and coworkers [60][61][62] have attempted to test Salam's conjecture that a phase transition should appear at a temperature T c $250 K, at which certain physical properties will become substantially different for D and L enantiomers.…”
Section: Intrinsic Asymmetries In Enantiomeric Pairsmentioning
confidence: 98%
“…5 Szabo-Nagy and Keszthelyi 59 claimed to detect a parity-violating difference in the CD spectra of cobalt(III) and iridium (III) salts of tris(ethanediamine). Wang and coworkers [60][61][62] have attempted to test Salam's conjecture that a phase transition should appear at a temperature T c $250 K, at which certain physical properties will become substantially different for D and L enantiomers.…”
Section: Intrinsic Asymmetries In Enantiomeric Pairsmentioning
confidence: 98%
“…This non-mirror-image relation may be ascribed to some impurities, as claimed in several papers [68,71,73,117]. It may also infer other unknown reasons, such as an inherent mirror symmetry breaking at a global level upward, our universe scale [123,124] and macroscopic MPV effects [21,37,43,46,51,67,72,74]. The commercially available chiral alcohols shown above are very expensive compared to common chemicals.…”
Section: Optically Active Polymer Aggregates In the Ground Statementioning
confidence: 99%
“…[8] Keszthelyi and Szabó-Nagy have described a small enantiomeric excess found in polycrystalline material upon crystallization from racemic solutions of (þ)-and (À)-tartrate(2À) with either (þ)-and (À)-[Co(en) 3 ] 3+ or [Ir(en) 3 ] 3+ ions. [9] The authors of the latter two works have claimed that the observed partial deracemization is because of electroweak forces. Clearly, these preparations could only be successful under nonequilibrium conditions involving physical fields and/or autocatalytic chirality-amplification mechanisms.…”
mentioning
confidence: 98%